Fiberoptic endoscopic evaluation of swallowing and videofluoroscopy swallowing assessment in adults in residential care facilities: a scoping review protocol. Issue 3 (March 2020) - Birchall, Olga; Bennett, Michelle; Lawson, Nadine; Cotton, Susan; Vogel, Adam P.
ABSTRACT: Objective: This scoping review will identify and explore existing evidence on the use of instrumental swallowing assessment in the diagnosis and management of dysphagia in adults living in residential care facilities. Introduction: Oropharyngeal dysphagia is prevalent among adults living in residential care facilities. Videofluoroscopy and fiberoptic endoscopic evaluation of swallowing are instrumental assessment procedures commonly utilized in the evaluation of oropharyngeal dysphagia in hospital and community settings. However, little is known about the use of these procedures in residential care facilities. To ensure evidence-based assessment of oropharyngeal dysphagia and to guide future research, exploration of the current use and clinical utility of videofluoroscopy and fiberoptic endoscopic evaluation of swallowing in residential care facilities is needed. Inclusion criteria: Published and gray literature written in English from 2000 onward that discusses instrumental swallowing assessment of adults in residential care facilities will be included in the review. Methods: A three-step search strategy will be used to explore relevant literature. All citations and articles retrieved during the searches will be imported into a software application for systematic reviews. Once duplicates are removed, two reviewers will screen the titles and abstracts against predefined inclusion criteria. Information will be extracted from literature that meets the selection criteria using a purposefully developed charting form. The search strategy and results will be illustrated through a Preferred Reporting Items for Systematic Reviews and Meta-Analyses diagram. Key findings and their relationship to the research questions will be summarized in a chart and discussed in interpretive narrative form.